Assessment of nutrition in female judokas during the precompetitive body mass reduction period - Kwiatkowska-Pamula, A.; Kurylas, A.; Perenc, A.; Ziolko, E.; Zlotkowska, R.; Muc-Wierzgon, M. (Trends in Sport Sciences, 2017)
Researchers have noticed that the pre-competition nutrition system used by judo contestants in 80% deviates from proper nutrition. The overriding goal, of reaching the so-called "enter weight", combined with the lack of basic knowledge about proper nutrition, can lead to unintended negative results during competition and in the further perspective, when continuing a sports career. Aim of Study. The aim of the study was to assess the energy value and the intake of basic nutrients (carbohydrates, protein and fat) in the pre-competitive period. Material and Methods. The objectives were to examine the range of rapid weight loss (RWL) in the tested group of judokas and to specify the relationship between training experience and the RWL. A total of 15 female athletes training judo were assigned to this study. The criteria determining the inclusion in the study were both national judo team membership as well as belonging to one of the three weight categories. The tested athletes` diets were assessed using the 7-day recall method. The female athletes were asked to report their daily food intake for 7 days before a competition. The diets were assessed using the software of Meal Diary MR BIG v 4.92. The results were compared with the standard of Benardot, 2012. Results. In the tested group of female judokas, the energy value and intakes of basic nutrients were significantly different from those specified in the mentioned standard. The problem of RWL in this study appeared common as it affected 93.33% of the participants. The study did not reveal any relationship between training experience and RWL. Conclusion. In order to prevent the occurrence of problems related to the low intake of energy and basic nutrients, athletes, coaches and parents ought to be educated in terms of rational nourishment and consequences of RWL.